PSIKOEDUKASI EMPATI “TEPA SLIRA” SEBAGAI UPAYA PENCEGAHAN PERILAKU BULLYING PADA ANAK SEJAK EARLY CHILDHOOD - Dina Pratiwi Primadiaty; Fadila Sofiana; Benita Khansarisky; Annastasia Ediati (Inisiasi, 2023)
The phenomenon of bullying has recently been in the spotlight of Indonesian society. Bullying behavior will hinder children's growth in developing empathy and compassion for others. This research aims to determine the effect of empathy psychoeducation "TEPA SLIRA" to increase empathy and prevent bullying behavior in early childhood. This research uses a quasi-experimental research method with a pretest-posttest control group design. The subjects in this research were class A students at TK III Pertiwi, Perumda Tembalang, with a total of 40 students. This research uses an empathy scale instrument adapted from the Child Development Achievement Level Standards (20 items), Goleman (Utami, 2014) in the form of a behavioral checklist. Researchers used the Mann-Whitney comparison test to test the effectiveness of the intervention. The results of data analysis on the tolerance aspect proved to have increased significantly at p<0.05, with the total empathy score increasing. It can be concluded that the "TEPA SLIRA" psychoeducation program has been proven to increase student empathy.